2009
DOI: 10.1364/oe.17.013918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the far-field region of LEDs

Abstract: Versatility in the design of optical systems is one of the key features of light-emitting diodes (LEDs) that has attracted considerable attention. In the analysis of systems using LEDs, it is useful to know if the distance is far enough from the LED to allow the radiation pattern to be simulated by the point source approach. We propose three far-zone conditions for LED light modeling: the far-field distance, and for practical purposes the quasi far-field and minimum far-field distances. Different types of LEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…4. The components of r i (t) include a random noise (denoted by w i ), whose distribution is determined by (7), and in the faulty case, a fault signal (denoted by ϕ i ); i.e.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The components of r i (t) include a random noise (denoted by w i ), whose distribution is determined by (7), and in the faulty case, a fault signal (denoted by ϕ i ); i.e.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Recent research in the literature mainly focuses on analyzing the illumination distribution of a group of LEDs [4][5][6][7]. A group of LEDs are usually required to achieve a uniform illumination pattern [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…LIDCs show that the maximum intensity of a HP-LED is distributed about the angle of 45 [21,22]. HPLEDs were installed on a calculated distance (about 6e8 cm far) from the inner edge of photoreactor, in a way that their radiated intensity is smoothly and maximum distributed around the center of the cylinder mouth.…”
Section: Design and Preparation Of A Hp-led Photoreactormentioning
confidence: 99%
“…In 2008, the authors proposed and demonstrated a precise optical modeling algorithm that simulated light patterns for a light source in the midfield; the proposed model has since been applied in practice in relevant industries [33], [34], [37]. However, the modeling algorithm does not address color distribution.…”
Section: Modeling Algorithmmentioning
confidence: 99%